2019
DOI: 10.1080/20550340.2019.1639968
|View full text |Cite
|
Sign up to set email alerts
|

The use of discontinuous PEEK/carbon fiber thermoplastic moulding compounds for thick-section componentry

Abstract: The hot-pressing of discontinuous fiber moulding compounds (DFMCs) is an established way of forming geometrically complex components, however, it is not a simple process. Rapid and irreversible cure cycles hinder the use of thermoset resins, and thermoplastic resins offer inferior mechanical performance. The recent availability of DFMCs utilising a Polyether Ether Ketone (PEEK) matrix offer an alternative, combining the usability of thermoplastics with significantly enhanced mechanical properties. A novel manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…While fillers with high aspect ratio, such as carbon fiber, carbon nanotubes, carbon nanofiber, and glass fiber, primarily increase the mechanical properties by increasing the load bearing capacity; adding carbonaceous material in the form of particles or fibers to polymers also improve thermal and electrical properties of the composites [10]. Their effect on the tribological performance of PEEK has been reported for various CF concentrations, pressure (loads) [11,12] and orientation [13][14][15][16][17]. In general, the study on the effect of fiber orientation using long fibers have concluded that polymer composites with fiber's long axis orientation normal to the sliding surface show the best performance followed by those in where fibers are aligned lengthwise to the sliding direction 4 [18].…”
Section: Introductionmentioning
confidence: 99%
“…While fillers with high aspect ratio, such as carbon fiber, carbon nanotubes, carbon nanofiber, and glass fiber, primarily increase the mechanical properties by increasing the load bearing capacity; adding carbonaceous material in the form of particles or fibers to polymers also improve thermal and electrical properties of the composites [10]. Their effect on the tribological performance of PEEK has been reported for various CF concentrations, pressure (loads) [11,12] and orientation [13][14][15][16][17]. In general, the study on the effect of fiber orientation using long fibers have concluded that polymer composites with fiber's long axis orientation normal to the sliding surface show the best performance followed by those in where fibers are aligned lengthwise to the sliding direction 4 [18].…”
Section: Introductionmentioning
confidence: 99%